Colonial mediascapes : sensory worlds of the early Americas - Cohen, Matt, 1970-; Glover, Jeffrey (University of Nebraska Press, 2014)
"In colonial North and South America, print was only one way of communicating. Information in various forms flowed across the boundaries between Indigenous groups and early imperial settlements. Natives and newcomers made speeches, exchanged gifts, invented gestures, and inscribed their intentions on paper, bark, skins, and many other kinds of surfaces. No one method of conveying meaning was privileged, and written texts often relied on nonwritten modes of communication. Colonial Mediascapes examines how textual and nontextual literatures interacted in colonial North and South America. Extending the textual foundations of early American literary history, the editors bring a wide range of media to the attention of scholars and show how struggles over modes of communication intersected with conflicts over religion, politics, race, and gender. This collection of essays by major historians, anthropologists, and literary scholars demonstrates that the European settlement of the Americas and European interaction with Native peoples were shaped just as much by communication challenges as by traditional concerns such as religion, economics, and resources."--Provided by publisher.